Growth, characterization and photoconduction properties of Sb0.1Mo0.9Se2 single crystals grown by DVT technique. (December 2018) - Dixit, Vijay; Nair, Salil; Joy, Jolly; Vyas, C.U.; Solanki, G.K.; Patel, K.D.; Pathak, V.M.
Abstract: The present investigation deals with the preparation of antimony doped molybdenum di-selenide (Sb0.1 Mo0.9 Se2 ) single crystals and its application for detection of UV–Visible radiation. The chemical composition of the crystals grown by direct vapor transport (DVT) technique is confirmed by Energy Dispersive Analysis of X-rays (EDAX), while the morphological analysis is carried out using optical microscopy and Scanning Electron Microscopy. The grown crystals are characterized by powder X–ray diffraction technique to evaluate the structural properties of the material and are compared with that of the pure MoSe2 crystals grown under similar conditions. The XRD analysis revealed the hexagonal structure of the crystals. The indirect optical band gap of 1.39 eV, Urbach energy and steepness parameter were determined by UV–Visible spectroscopy. The ability of pure and Sb doped MoSe2 crystals to be used as detectors of UV, Visible and IR radiations are studied by their pulsed photoresponse on exposure to a polychromatic source at varying intensities of illumination. Laser source (670 nm) having an intensity of 3 mW cm −2, UV radiation (320 nm) having an intensity of 20 mW cm −2 and IR radiation having an intensity of 120 mW cm −2 were used in the measurements. The effect of biasing voltage on the photoresponse has also been analyzed. The excellent detection properties of the grown crystals are revealed from the responsivity, specific detectivity and external quantum efficiency (EQE) of pure and Sb doped MoSe2 crystals. The effect of doping is clearly seen in the improvement of the detection properties of the crystals.